DEVELOPMENT OF STUDENT WORKSHEETS WITH A REALISTIC MATHEMATICS EDUCATION APPROACH SET MATERIAL CLASS VII JUNIOR HIGH SCHOOL: PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK MATERI HIMPUNAN KELAS VII SMP - Baharuddin; Nurul Hasfika Sari; Andi Ika Prasasti Abrar; Fitriani Nur; Andi Dian Angriani (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
The Realistic Mathematics Education (RME) approach is one of the approaches that seeks to link mathematical concepts with situations that are relevant and meaningful to students, thus helping them understand these concepts better. Therefore, this approach is important to be integrated into learning, one of which is through the Learner Worksheet. This research aims to develop Learner Worksheets using the Realistic Mathematics Education approach that is valid, practical, and effective. This research is development research with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. The research trial design involved the subject of VII grade students of SMPN 23 Sinjai, Sinjai Regency. Data collection instruments include instrument validation sheets, learner worksheet implementation sheets, learner response questionnaires, teacher response questionnaires, learner activity observation sheets, learning management observation sheets, and learning outcomes tests. The results showed that the Learner Worksheets using the Realistic Mathematics Education approach that had been developed met the criteria of validity, practicality, and effectiveness. This research contributes to providing Realistic Mathematics Education-based Student Worksheets that are valid, practical, and effective so that they can improve the quality of mathematics learning in the classroom.